2016
DOI: 10.1142/s0219581x16400056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Control Coefficients on the Performance of CNTFET Under Different Parameters

Abstract: This paper deals with the performance of both gate and drain control coefficients to analyze the behavior of carbon nanotube field effect transistors (CNTFETs) under ballistic conditions and based on the change of different parameter value, such as oxide thickness of structure and temperature variation. A thorough study of both gate and drain control coefficient effects on the performance of CNTFETs has been conducted under different temperature and oxide layers and the output of the device has been analyzed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In more details, the electrical properties of chemFETs are derived from measuring its drain-source current I ds as a function of gate V g and drain voltage V d . From these curves are extracted synthetic parameters such as: (i) in the linear regime of I ds as a function of V d , the (gate-voltage controlled chemFET resistance (slope of I ds (V d )); (ii) the ratio between ON and OFF current levels (values of I ds when the semiconducting channel is respectively in its most conducting—ON—and most insulating—OFF—state); (iii) the transconductance (the maximum value of the first derivative of I ds (V g ), which is related to the mobility of the semiconducting channel); (iv) the threshold voltage (gate voltage value for which the semiconducting channel transitions from insulating to conducting); (v) the hysteresis observed between threshold voltage values or transconductance values during upward and downward sweep of the gate voltage [ 93 , 94 , 95 ]. Regarding the latter, this hysteresis is attributed in large part to the adsorption of water molecules on the device surface creating charging effect [ 96 ].…”
Section: Operating Principles Of Cnt-based Chemical Sensorsmentioning
confidence: 99%
“…In more details, the electrical properties of chemFETs are derived from measuring its drain-source current I ds as a function of gate V g and drain voltage V d . From these curves are extracted synthetic parameters such as: (i) in the linear regime of I ds as a function of V d , the (gate-voltage controlled chemFET resistance (slope of I ds (V d )); (ii) the ratio between ON and OFF current levels (values of I ds when the semiconducting channel is respectively in its most conducting—ON—and most insulating—OFF—state); (iii) the transconductance (the maximum value of the first derivative of I ds (V g ), which is related to the mobility of the semiconducting channel); (iv) the threshold voltage (gate voltage value for which the semiconducting channel transitions from insulating to conducting); (v) the hysteresis observed between threshold voltage values or transconductance values during upward and downward sweep of the gate voltage [ 93 , 94 , 95 ]. Regarding the latter, this hysteresis is attributed in large part to the adsorption of water molecules on the device surface creating charging effect [ 96 ].…”
Section: Operating Principles Of Cnt-based Chemical Sensorsmentioning
confidence: 99%
“…The literature shows that research on PA6/ND composites is very sparse. 34 The objective of the study reported here was to explore the morphological evolution and mechanical properties enhancement of PA6 in the presence of ND. The primary focus was to examine the role of surface functionality of ND.…”
Section: Introductionmentioning
confidence: 99%
“…The tube between source and drain is called channel. 15 To understand this flow of electrons from source to drain, first we need to see all energy bands between the two potential sources. Figure 4 shows that different energy bands are just between source and well.…”
Section: Approachmentioning
confidence: 99%